2022
DOI: 10.1002/alz.12577
|View full text |Cite
|
Sign up to set email alerts
|

The P522R protective variant of PLCG2 promotes the expression of antigen presentation genes by human microglia in an Alzheimer's disease mouse model

Abstract: The P522R variant of PLCG2, expressed by microglia, is associated with reduced risk of Alzheimer's disease (AD). Yet, the impact of this protective mutation on microglial responses to AD pathology remains unknown. Chimeric AD and wild-type mice were generated by transplanting PLCG2-P522R or isogenic wild-type human induced pluripotent stem cell microglia. At 7 months of age, single-cell and bulk RNA sequencing, and histological analyses were performed. The PLCG2-P522R variant induced a significant increase in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 48 publications
1
25
0
Order By: Relevance
“…Our single-nuclei RNA-seq analysis data indicated that PLCG2 variants regulate the composition of microglial clusters in the AD brain. These results were consistent with our previous analysis of AD chimeric mice with xenografted human iPSC-derived microglia expressing PLCG2 P522R (Claes et al, 2022), in which the proportions of microglia enriched in Spp1, Fabp5, and Cd74 were elevated. Moreover, 5xFAD P522R mice exhibit a plaqueresponsive microglial subcluster enriched in Hcar2, a microglial receptor we recently identified to be required for efficient and neuroprotective microglial responses to amyloid pathology (Moutinho et al, 2022).…”
Section: Discussionsupporting
confidence: 93%
“…Our single-nuclei RNA-seq analysis data indicated that PLCG2 variants regulate the composition of microglial clusters in the AD brain. These results were consistent with our previous analysis of AD chimeric mice with xenografted human iPSC-derived microglia expressing PLCG2 P522R (Claes et al, 2022), in which the proportions of microglia enriched in Spp1, Fabp5, and Cd74 were elevated. Moreover, 5xFAD P522R mice exhibit a plaqueresponsive microglial subcluster enriched in Hcar2, a microglial receptor we recently identified to be required for efficient and neuroprotective microglial responses to amyloid pathology (Moutinho et al, 2022).…”
Section: Discussionsupporting
confidence: 93%
“…Recent studies have suggested that the P522R variant is a mild hypermorph [ 15 17 ], serving to potentiate the enzymatic activity of the protein, thus impacting on its downstream targets. It has been shown that this altered activity appears to enhance macrophage phagocytic activity and enhance cytokine release in response to inflammatory stimulation, and may promote microglial activation [ 17 ], priming them to adopt an MHC class II state, that is notably reduced in AD brains [ 18 ]. Conversely however, other studies have suggested that in fact phagocytic clearance is impaired, while endocytic clearance is enhanced [ 15 ], hence its exact impact on phagocytic vs. endocytic clearance of AD relevant cargoes is still unclear.…”
Section: Introductionmentioning
confidence: 99%
“…A PLCγ2-P522R knock-in mouse model was established to assess the role of the protective variant in immune cells, which showed that the PLCγ2-P522R variant promoted microglial immune functions [90]. Besides, the PLCγ2-P522R variant increases the capacity of human microglia to present antigens and promoted the recruitment of CD8 + T cells to the brain in AD mouse models [91]; however, the role of the PLCγ2-P522R variant in the crosstalk between microglia and T cells in AD requires further study.…”
Section: Phospholipase C Gamma 2 (Plcg2)mentioning
confidence: 99%